Evaluating nose and throat cancer risk : Number sense and taboos on ill-health - Ting, Su Hie; Jerome, Collin; Podin, Yuwana; Sharifah Sophia, Wan Ahmad (2018)
The threat posed by a disease depends on perceptions of the severity of the disease and an individual’s perceptions of their risk or susceptibility of getting the disease. Studies have indicated that the public has difficulty understanding risk assessment in numerical form. This study examined the public’s reactions when asked to evaluate their risk of getting nasopharyngeal cancer, also known as nose and throat cancer. Semi-structured interviews were conducted with 32 participants in Kuching, Sarawak (14 urban, 18 rural) to elicit personal evaluations of susceptibility and perceived risk factors of nose and throat cancer. The results indicated that the participants faced problems in putting a numerical figure to their risk of getting nose and throat cancer. More interestingly, some participants interviewed hesitated to estimate their risk of getting nose and throat cancer because of taboos on ill-health. They felt that if they assessed their risk to be high, they might be cursing themselves with the disease. On the other hand, if they assessed their risk to be low, they did not believe in God’s control over their lives. The perceived risk factors of nose and throat cancer were lifestyle and environmental factors as well as genetic factors. The findings suggest that to promote better awareness of nose and throat cancer, it is necessary to design culturally and intellectually appropriate cancer risk messages so that the target audience are motivated to make behavioural changes to minimise risk of getting the cancer or to seek early detection of the cancer.